THE ASSISTANCE (MEDEPLICHTIGE) BY CHILDREN LEADING TO THE OCCURRENCE OF CRIMINAL ACTS - Athalie Aisyah Prameswari (Master of Law Faculty of Law UNISSULA, 2023)
This study is related to a case of assault in which the parents of the victim are prominent figures in GP Ansor. The study investigates the manner in which the juvenile AG, who is underage, participated in the assault crime. The premise of this study is that the legal safeguards for children who are in legal trouble (ABH) have not been applied correctly. The description of the legal protection offered to all children who aid in incidents of abuse is what makes this research novel. Law Number 11 of 2012 Concerning the Juvenile Criminal Justice System was developed to ensure that all children's rights, including those of children who are in legal trouble, to live, grow, develop, and engage maximally in accordance with human dignity are guaranteed. Normative juridical is used in this research through a statutory approach, using secondary data sources supported by primary and secondary legal materials. The results of the research show that according to the results of Court Decision Number 4/Pid.Sus-Anak/2023/PN.JKT.SEL which has permanent legal force, AG's child's role as a child who assists in criminal acts of abuse is appropriate, however the decision given judged by the judge to be inappropriate. Reviewing various aspects along with existing laws and regulations, it would be more appropriate to impose a second subsidiary sentence, namely Article 353 Paragraph (2) of the Criminal Code (KUHP) juncto Article 56 2nd of the Criminal Code, which reduces the sentence for AG Children, is the best choice.